The present and future directions of metaverse, artificial intelligence, and second life environments in new language education within higher education: A systematic review (Journal of Applied Learning and Teaching, 2025)
The Metaverse, Artificial Intelligence (AI), and Second Life (SL) environments signify the commencement of the next phase in educational revolution, which offers the opportunity to seamlessly integrate digital and physical realms in a multiuser immersive setting. Despite the substantial potential for harnessing the Metaverse, AI, and SL in the domains of learning and teaching, a notable deficiency exists in research investigating the benefits, challenges, and solutions of these technologies for language acquisition. This review aims to address this deficiency by examining the potential advantages, challenges, and future directions of these technologies within the context of language education. It analyses relevant studies from ScienceDirect, Emerald, SAGE, SpringerLink, IEEE Xplore, and JSTOR, which focus on studies from 2011 to 2025. Key findings reveal the benefits of Metaverse, AI, and SL, such as improved awareness, knowledge access, motivation, engagement, and support. These technologies contribute significantly to enhancing language learning and pedagogy. The challenges include ethical concerns, socio-emotional issues, and a lack of proficiency in educational virtual technologies. Nevertheless, the study provides constructive implications and solutions for integrating these technologies into language education, enhancing understanding of their benefits in new language education, while recommending how to incorporate them into higher education pedagogy.